1989
DOI: 10.1021/bi00448a036
|View full text |Cite
|
Sign up to set email alerts
|

Role of the stereochemistry of the hydroxyl group of cholesterol and the formation of nonbilayer structures in phosphatidylethanolamines

Abstract: The phase behavior of mixtures of cholesterol or epicholesterol with phosphatidylethanolamine was studied by differential scanning calorimetry and by X-ray diffraction. Discrete domains of cholesterol are detected by X-ray diffraction in the L alpha phase of phosphatidylethanolamine from egg yolk and synthetic dielaidoylphosphatidylethanolamine beginning at mole fractions of 0.35-0.4 cholesterol. Separate domains of crystalline epicholesterol can also be detected in the L alpha phase of dielaidoylphosphatidyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 41 publications
5
61
0
Order By: Relevance
“…At low concentrations (up to around 15-20% of the total membrane lipids), CHO favored the binding of G␣ proteins to lipid bilayers, but at higher concentrations (30-50 mol% CHO) it impaired this binding. The ability of this lipid to induce nonlamellar structures at low mol fractions (less than 0.2) and inhibit them at higher mol fractions would explain the biphasic behavior of the G␣i binding to CHO-containing membranes (25). On the other hand, CHO intercalates in the surface of the lipid leaflet, a potential target for the binding of the G protein fatty acid moiety, which favors the interaction between G proteins and membranes (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…At low concentrations (up to around 15-20% of the total membrane lipids), CHO favored the binding of G␣ proteins to lipid bilayers, but at higher concentrations (30-50 mol% CHO) it impaired this binding. The ability of this lipid to induce nonlamellar structures at low mol fractions (less than 0.2) and inhibit them at higher mol fractions would explain the biphasic behavior of the G␣i binding to CHO-containing membranes (25). On the other hand, CHO intercalates in the surface of the lipid leaflet, a potential target for the binding of the G protein fatty acid moiety, which favors the interaction between G proteins and membranes (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the enantiomer of cholesterol ( ent -cholesterol) could restore ligand binding and receptor signaling after cholesterol-depletion, whereas the diastereomer ( epi -cholesterol) did not (Jafurulla et al, 2014). Epi -cholesterol was shown before to have different biophysical effects on the bilayer due to different tilt angles and phase transition characteristics (Cheetham et al, 1989). The ligand-independent oligomerization of serotonin 5-HT 1 A receptors in living cells was observed with FRET and appeared to be enhanced upon acute cholesterol depletion (Paila et al, 2011).…”
Section: Specific Membrane Components Influence Gpcr Oligomerizatimentioning
confidence: 99%
“…While ent -cholesterol shares identical physicochemical properties with cholesterol, previous studies have shown that the biophysical properties of epi -cholesterol and native cholesterol are different (Westover and Covey, 2004; Covey, 2009). epi -Cholesterol has been reported to differ in its tilt angles, condensing ability, and phase transition properties from cholesterol in membranes (Demel et al, 1972; Dufourc et al, 1984; Murari et al, 1986; Cheetham et al, 1989). We show here that cholesterol and ent -cholesterol share comparable ability in increasing membrane dipole potential.…”
Section: Introductionmentioning
confidence: 99%